Comparing the microflora of the conjunctiva and contact lens in therapeutic soft contact lens wearers (Ukrainian Journal of Ophthalmology, 2025)
Background: More than 125 million (2%) people worldwide wear contact lenses (CL). Rates of CL-associated infections increase with an increase in frequency of wear of CL.Purpose: To compare the bacterial and fungal microflora of the conjunctiva and contact lens in therapeutic soft contact lens (SCL) wearers.Material and Methods: We examined the microflora of the conjunctival surface in 80 therapeutic SCL wearers and of the SCL surface in 235 relevant lenses. Monthly therapeutic SCLs that were discarded after being replaced were sent for bacteriological and mycological culture. We used only the data for the years 2016 through 2019 in the analysis.Results: Pathogenic and/or opportunistic agents were found in samples from 121 SCL (51.5%). Gram positive, Gram negative and fungal species were found in 63.5%, 29.5%, and 7.0%, respectively, of the 121 SCL. Mixed microflora was evident in 14.1% of the 121 SCL. Organisms were isolated from the conjunctiva of 51 (63.8%) of 80 patients. Gram positive, Gram negative and fungal species were found in 75.0%, 20.0%, and 5.0%, respectively, of patients. Mixed microflora was evident in 14.1% of patients.Conclusion: Organisms were isolated from the conjunctiva of 51 (63.8%) of 80 therapeutic SCL wearers and from 121 (51.5%) of 235 SCL (p = 0.06). Conjunctival swabs and SCL swabs harbored pathogenic microorganisms on 26.2% and 26.9% of occasions, respectively. On 32.5% of occasions, there was a difference in species isolated from conjunctival swabs and SCL swabs. This stresses the need for microbiological studies of the conjunctiva and contact lenses in SCL wearers.
Keywords: microbiological studies; conjunctiva; soft contact lens; bacterial flora; fungal flor; antibacterial agents